2017
DOI: 10.1177/0309364616628341
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender, level of amputation and diabetes on prosthetic fit rates following major lower extremity amputation

Abstract: Background:Diabetes mellitus is a leading cause of major lower extremity amputation.Objective:To examine the influence of gender, level of amputation and diabetes mellitus status on being fit with a prosthetic limb following lower extremity amputation for peripheral arterial disease.Study design:Retrospective analysis of the Scottish Physiotherapy Amputee Research Group dataset.Results:Within the cohort with peripheral arterial disease (n = 1735), 64% were men (n = 1112) and 48% (n = 834) had diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 36 publications
(91 reference statements)
1
29
1
1
Order By: Relevance
“…However, most studies [30][31][32][34][35][36] had a small sample size and/or did not report outcomes for different amputation levels. Davie-Smith et al [29] as well as Resnik et al [33] found fit rates in transfemoral amputees of 21.6% and 19.2%, respectively. While Davie-Smith et al [29] analyzed age effects separately for transfemoral and transtibial amputations, Resnik et al [33] reported only a combined age coefficient.…”
Section: Epidemiologymentioning
confidence: 96%
See 4 more Smart Citations
“…However, most studies [30][31][32][34][35][36] had a small sample size and/or did not report outcomes for different amputation levels. Davie-Smith et al [29] as well as Resnik et al [33] found fit rates in transfemoral amputees of 21.6% and 19.2%, respectively. While Davie-Smith et al [29] analyzed age effects separately for transfemoral and transtibial amputations, Resnik et al [33] reported only a combined age coefficient.…”
Section: Epidemiologymentioning
confidence: 96%
“…Davie-Smith et al [29] as well as Resnik et al [33] found fit rates in transfemoral amputees of 21.6% and 19.2%, respectively. While Davie-Smith et al [29] analyzed age effects separately for transfemoral and transtibial amputations, Resnik et al [33] reported only a combined age coefficient. Hence, we applied data from Davie-Smith et al [29].…”
Section: Epidemiologymentioning
confidence: 96%
See 3 more Smart Citations